Effect of the Increase in Vertical Web Member Stiffness on Lateral Buckling Strength of the Pony Steel Bridge - Sugihardjo, Hidajat; Suswanto, Budi; Rosyidi, Moh Fadhlan (Institut Teknologi Sepuluh Nopember, 2025)
In half-through bridge or pony steel bridge, that is a bridge without upper wind bracing, strength of the bridge is determined mainly by the lateral buckling strength of its upper chord. Buckling strength of this chord is provided by the flexural stiffness of vertical web member, cross beam, and diagonal beam. In order to improve the stiffness of vertical web member, triangular steel profile that was quite high was added to the inner side of bridge for reducing the clearance width in bridge and disturbing traffic or pedestrian. In this research, stiffness of the vertical web member was improved by using the non-prismatic cross section and adding the triangular stiffener as high as the concrete deck. Finite Element Analysis for the lateral stiffness of bridge cross section used a 3D element model which has been validated by previous study. This numerical study was conducted to validate the Engesser theory for determining the lateral elastic stiffness from upper chord. Study shows the result that accuracy of 3D element model is extremely high, compared with analytic method. Lateral elastic stiffness of bridge in general increased along with the stiffness of vertical web member. However, it can be concluded that effect on the capability of lateral buckling in upper chord was not too significant, as a consequence of the increase in stiffness of vertical web member. Critical lateral buckling occurred in an inelastic range, in which the critical inelastic buckling stress was determined using small tangent modulus as alternative of modulus of elasticity.